Assessing the effects of different prebiotic dietary oligosaccharides in sheep milk ice cream. (January 2017) - Balthazar, C.F.; Silva, H.L A.; Vieira, A.H.; Neto, R.P.C.; Cappato, L.P.; Coimbra, P.T.; Moraes, J.; Andrade, M.M.; Calado, V.M.A.; Granato, D.; Freitas, M.Q.; Tavares, M.I.B.; et al.
Abstract: The objective of this study was to assess the effects of different prebiotic dietary oligosaccharides (inulin, fructo-oligosaccharide, galacto-oligossacaride, short–chain fructo-oligosaccharide, resistant starch, corn dietary oligosaccharide and polydextrose) in non-fat sheep milk ice cream processing through physical parameters, water mobility and thermal analysis. Overall, the fat replacement by dietary prebiotic oligosaccharides significantly decreased the melting time, melting temperature and the fraction and relaxation time for fat and bound water (T22 ) while increased the white intensity and glass transition temperature. The replacement of sheep milk fat by prebiotics in sheep milk ice cream constitutes an interesting option to enhance nutritional aspects and develop a functional food. Graphical abstract: Highlights: Prebiotic dietary oligosaccharides to replace fat in sheep milk ice cream formulation Improvement the intensity of whiteness and lightness in prebiotic dietary oligosaccharides sheep milk ice cream Smaller ice crystals and decreased melting time, melting temperature and T22 values Increased glass transition temperature